Moulds in floor dust – a particular problem in mechanically ventilated rooms? A study of adolescent schoolboys under the Danish moulds in buildings program - Meyer, Harald William; Suadicani, Poul; Nielsen, Peter A.; Sigsgaard, Torben; Gyntelberg, Finn (Scandinavian Journal of Work, Environment & Health, 2011)
' ' OBJECTIVE ': 'To test the hypothesis that the association between levels of mould in floor dust and prevalence of potentially building-related symptoms may depend on the type of ventilation. ' ' METHODS ': 'This stratified cross-sectional study is part of the Danish moulds in buildings program (DAMIB), including 503 adolescent schoolboys aged 13–17 years at 15 schools. Besides assessing symptom prevalences in questionnaires, we measured numerous potential risk factors in the school buildings. ' ' RESULTS ': 'Stratifying on type of ventilation (natural, exhaust only, or full mechanical ventilation system), the negative effect of high levels of mould in floor dust was more pronounced in rooms with mechanical ventilation system. With a variable combining high level of moulds in floor dust with type of ventilation in the classroom, a significantly increased risk was found for all symptoms in the mechanically ventilated classrooms with high mould concentrations. In multiple logistic regression models, significant odds ratios (OR) ranged from 3.9 [95% confidence interval (95% CI) 1.5–10.1] (nasal congestion) to 17.0 (95% CI 2.1–138) (dizziness). ' ' CONCLUSIONS ': 'The combined effect of moulds in dust and ventilation form might be a result of the higher air flow keeping the dust in the breathing zone for a longer time, thereby increasing the exposure for the occupants of the classrooms. It is important in future indoor air research also to focus on the combination effects of risk factors, including the type of ventilation.
Keywords: building-related symptom; combined effect; DAMIB; Danish moulds in buildings program; dust; floor dust; fungi; mechanical ventilation; mold; mould; pupil; school